EFEKTIVITAS METODE SMALL GROUP DISCUSSION PADA HASIL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMKN 2 TENGGARONG - Riadi, Akhmad; Misran, Misran (AZKIYA, 2022)
The Small Group Discussion method or group discussion method in research is an alternative method used by teachers in class, aimed at solving a problem based on the opinions of students. While learning Islamic religious education is a teaching and learning process in Islamic religious education which includes religious elements such as aqidah, morals, jurisprudence, the Koran, hadith and the history of Islamic culture to shape the personality of students so that they become individuals who have good morals in accordance with Islamic religious goals, the more the better the discussion method used in Islamic religious education subjects, the better the results achieved by students, conversely if the discussion method is carried out in Islamic religious learning, the results achieved will not be optimal or inadequate. greatly determines the quality of learning, because accuracy in selecting learning strategies can support the success of learning activities so that it will increase student achievement. So far, PAI learning used at SMKN 2 Tenggarong is conventional learning, teachers also don't really understand learning strategies, for example small group discussions in this lesson so that many students pay less attention to the lessons being delivered. The method used in this research is the experimental method. The findings of this study are that the use of active learning strategies Small Group Discussion is effective in increasing learning achievement in Islamic religious education.